Aktualisasi Dari Tokoh Milea Dalam Novel Dilan 1990 Karya Pidi Baiq Berdasarkan Teori Humanistik Abraham Maslow - Erick Kurniawan; Ventiano Adi Pamungkas; Eva Dwi Kurniawan (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This journal aims to analyze the process of self-actualization of the main character in the 1990 novel Dilan by Pidi Baiq based on Abraham Maslow's humanistic theory. This theory is used because according to Maslow the psychological life of human beings has stratified needs. This study used quantitative descriptive method. The source of data in this study is the 1990 novel Dilan by Pidi Baiq. Data collection is carried out by analyzing and analyzing literary works that are the main source of research, identifying data and linking with Abraham Maslow's theory. Abraham Maslow's humanistic needs are physiological needs, security needs, love and existence needs, self-esteem needs and self-actualization needs. Self-actualization is the highest human need, where the individual reaches his maximum potential and becomes his true self. In Dilan's novel, Milea's character experiences significant changes and growth through her love story. He is able to meet physiological needs, security, love and belonging, appreciation, and self-actualization, including privacy, separation from the environment, and social interests. This shows that Milea has reached the highest level in the hierarchy of human needs according to Maslow.